Near‐Infrared Shielding: Enhanced Near‐Infrared Shielding and Light Scattering Using Surface‐Roughened Hybrid Hollow Microparticles Synthesized with Polymer and TiO2@Al(OH)3 for Cosmetic Applications (Part. Part. Syst. Charact. 6/2018). (22nd June 2018) - Han, Nuri; Kim, Min Gyu; Kim, Sung Wook; Shin, Min Kyu; Kim, Su Ji; Kim, Moo Sung; Lee, Sang Rin; Lee, Jun Bae; Pyun, Seung Beom; La, Ju A; Song, Ji Eun; Cho, Eun Chul
Abstract : A surface‐roughened hybrid hollow microparticle bearing TiO2 @Al(OH)3 colloids for near‐infrared shielding with a high light scattering efficiency is reported by Nuri Han, Min Gyu Kim, and co‐workers in article number1800057 . A cosmetic formulation with the particles suppresses the increase in artificial skin temperatures under a simulated sunlight.